Spectral Anatomies: Heritage, Hauntology and the 'Ghosts' of Varosha. Issue 1 (1st May 2014) - Sterling, Colin
This paper unravels the idea of the 'ghost town' - and more specifically the deserted district of Varosha, Famagusta - as it relates to heritage, questioning the discursive dynamics and affective potential of what can seem a trite and therefore hollow phrase. Drawing on apposite theories of hauntology (Derrida 1993 ) and the ghosts of place (Bell 1997 ) I argue that there is a dense back-and-forth between two distinct positions in this term, both of which play into wider heritage processes. The first understands the ghost town as an empty if uniquely atmospheric space, ripe for development or 'dark tourism' (Lennon and Foley 2000 ). Heritage is implicated here in the protection and promotion of sites which may be perceived as 'ruin porn' - by turns melancholy and exhilarating but fundamentally removed from contemporary life. The second position unsettles this reading by focusing on the complexities of the very word 'ghost', here understood as 'the sense of the presence of those who are not physically there' (Bell 1997: 813 ). From this perspective, common heritage practices (including collecting, exhibiting, and narrating) might be seen as an attempt to psychologically re-inhabit vacant places, a process which takes on extra significance around the highly politicised context of Varosha. Through fieldwork, archival research and intertextual and visual analysis I track the description of Varosha as a ghost town across journalism, contemporary art and diasporic discourse, in the process anatomising this spectral designation to reconceptualise its wider relevance to heritage.